Direct observation of room-temperature out-of-plane ferroelectricity and tunneling electroresistance at the two-dimensional limit - H. Wang (Nature Portfolio, 2018)
High temperature perpendicular ferroelectricity in nano thin films is crucial for miniaturization of electronic devices. Here the authors show the presence of stable and switchable out-of-plane ferroelectricity in tetragonal BiFeO3 thin films at the two-dimensional limit and 370% tunneling electroresistance in ferroelectric tunnel junctions.